Association between Children's Imaginational Overexcitability and Parent‐Reported Creative Potential: Cognitive and Affective Play Processes as Potential Mediators. (27th April 2021) - Fung, Wing Kai; Chung, Kevin Kien Hoa; He, Mavis Wu‐jing
Abstract: This study examined the direct and indirect associations among imaginational over‐excitability, cognitive play processes, affective play processes, and parent‐reported creative potential of Hong Kong Chinese kindergarten children. Participants were 106 parents of local kindergarten children (43.4% girls, mean age = 60.1 months). Parents reported their child's imaginational over‐excitability, cognitive play processes, affective play processes, and creative potential through a questionnaire. Results from the path model revealed that children's imaginational over‐excitability was positively associated with their cognitive and affective play processes. Children's parent‐reported creative potential was significantly related to their cognitive play processes but marginally related to their affective play processes. Furthermore, the relationship between imaginational over‐excitability and parent‐reported creative potential was fully mediated by children's cognitive and affective play processes. Theoretically, the findings suggest that children's cognitive and affective play processes may explain the association between their imaginational over‐excitability and parent‐reported creative potential. Practically speaking, the results highlight the importance of providing imaginative children with opportunities and supports to carry out imaginative pretend play so as to promote their creative potential.